Dual-target tDCS and dual-task training modulate neuroinflammation and neuroplasticity: transcriptomic and behavioral evidence in stroke rehabilitation - Fu, Yutong; Yan, Qianxi; Wang, Anjuan; Zhang, Hongmei; Wang, Wenli; Yao, Liqing (Frontiers in Rehabilitation Sciences, 2025)
BackgroundTranscranial direct current stimulation (tDCS) combined with dual-task training (DTT) has shown potential in promoting neurorehabilitation. However, the transcriptomic mechanisms underlying the synergistic effects of dual-target tDCS remain unexplored. This study aims to evaluate the effects of tDCS + DTT on cognitive and motor functions and preliminarily explore its molecular basis through transcriptomic analysis.MethodsFifty two chronic stroke patients were randomized to receive dual-target tDCS (anodal electrodes over affected primary motor cortex M1 and left dorsolateral prefrontal cortex DLPFC) combined with DTT (n = 26) or sham stimulation with DTT (n = 26). Behavioral assessments, including the Visual Cognitive Assessment Test (VCAT), Hamilton Depression Scale (HAMD), Fugl-Meyer Lower Limb Assessment (FMA-L), Timed Up and Go Test (TUG), and Modified Barthel Index (MBI), were conducted before and after the intervention. Peripheral blood transcriptomic analysis was performed on a subset of patients from the tDCS + DTT group to identify differentially expressed genes (DEGs) and enriched pathways.ResultsSignificant interactions were observed for VCAT (p < 0.001), MBI (p = 0.033), HAMD (p < 0.001), FM-L (p < 0.001), TUG-CMDT time (p < 0.001), and TUG-CMDT accuracy rate (p < 0.001). Transcriptomic analysis revealed 1,319 DEGs post-treatment, predominantly downregulating inflammation/apoptosis-related genes (1,155) and upregulating neuroplasticity-associated genes (164). KEGG pathway analysis highlighted suppressed NF-κB signaling and apoptosis pathways, alongside enhanced synaptic plasticity mechanisms. Key regulatory genes, such as PPP1R15A, BCL3, GADD45B, and NFKBIA, were identified as potential mediators of tDCS-induced neuroprotection.ConclusionDual-target tDCS combined with DTT promotes functional recovery in stroke patients through transcriptomic reprogramming of inflammatory and neuroplastic pathways, offering a novel strategy for multi-modal neurorehabilitation.